SUN-747 Steroid Hormone Metabolism Mediated Racial Disparity in Men with Benign Prostatic Hyperplasia - Liu, Teresa T (J Endocr Soc, 2020)
Introduction and Objective: Racial disparity in prostate cancer has been well established, with African American (AA) men having higher rates of diagnoses and death from the disease compared to Caucasian American (CA) men. AA men also have a high incidence of benign prostatic hyperplasia (BPH), a disease associated with lower urinary tract symptoms (LUTS) that affect >210 million men worldwide. Furthermore, AA men with BPH have an increased incidence of non-surgical treatment failure, larger prostates at time of surgery, and surgery occurring at a younger age. The use of selective estrogen receptor modulators (SERMs) in the treatment of BPH has been proposed, as an increase in ERα has been associated with disease progression. AA men have higher levels of circulating estrogens as compared to CA leading to an increased prenatal exposure to estrogens. Estrogen exposure has been shown to alter the epigenetic landscape of genes, and this prenatal exposure to estrogens could sensitize the AA men to altered steroid homeostasis leading to an increase susceptibility to BPH and an altered response to treatment. In this study, we examine the prostate expression and localization changes in estrogen receptors (ERα, ERβ) as well as steroid metabolism genes in AA and CA with or without BPH. Methods: To examine the impact of race on BPH, we examined prostate tissue from 66 men. We utilized 21 normal transition zone controls from radical prostatectomies, 8 normal transition zone controls from organ donors, and 37 BPH samples divided between CA and AA men. Using multispectral quantitative multiplex IHC, we examined the steroid hormone related protein expression of ERα, ERβ, CYP7B1, and AKR1C1 on each FFPE tissue section. We quantified the optical density of each protein of interest as well as examined colocalization and coexpression through cell and tissue segmentation. Results: In CA men, there is a dysregulation of ERα:ERβ homeostasis with BPH relative to normal as an increase in ERα and a decrease in ERβ expression was observed. Furthermore, an increase in CYP7B1, an enzyme that degrades ERβ ligands, was also observed. In AA men, we observed no difference between normal and BPH states, however in both normal and BPH prostate tissues, ERα and ERβ were increased relative to CA men. In addition, there is a decrease in AKR1C1, the enzyme that metabolizes DHT to an ERβ ligand. Conclusions: Our study supports the concept that differences in hormone pathways exist between AA and CA men. Understanding how these racial difference in steroid metabolism enzymes as well as ERs between CA and AA men with BPH could enhance treatment strategies for men with BPH.